2018
DOI: 10.1002/pssb.201800427
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sn/Ge Cation Exchange on Vacancy‐Ordered Double Perovskite Cs2Sn(1−x)GexI6: A First‐Principles Theoretical Study

Abstract: The toxicity of lead (Pb) and the volatility of organic cations in the typical Pb‐based organic–inorganic hybrid perovskite materials are the two key challenges in the emerging perovskite solar cells (PSCs). Thus, the development of lead‐free and inorganic perovskite materials for solar cells is very important. Here, the mixed vacancy‐ordered inorganic double perovskite Cs2Sn(1−x)GexI6 is studied to explore how gradual substitution of tetravalent gemanium (Ge4+) for tetravalent tin (Sn4+) influences the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…When compared to CsSnI 3 , CsGeI 3 does display, however, inferior optoelectronic properties owing to the lone‐pair effect [20] and relatively larger E g . Inspired by the heterovalent B‐site co‐alloying strategy for Pb and Sn, several reports have proposed to mix Sn with Ge for a new candidate of mixture lead‐free perovskite [21–26] . By first‐principles computations, Ju et al.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to CsSnI 3 , CsGeI 3 does display, however, inferior optoelectronic properties owing to the lone‐pair effect [20] and relatively larger E g . Inspired by the heterovalent B‐site co‐alloying strategy for Pb and Sn, several reports have proposed to mix Sn with Ge for a new candidate of mixture lead‐free perovskite [21–26] . By first‐principles computations, Ju et al.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Sn‐based PSC devices have recently shown promising PCE approaching 10% . Nevertheless, the easy oxidization of Sn 2+ to Sn 4+ and Ge 2+ to Ge 4+ leads to the instability of PSC devices in ambient condition, which remains the biggest challenge in Sn‐ or Ge‐based PSCs . In addition to Sn or Ge, another candidate for the substitution of Pb 2+ is non‐toxic Bi 3+ and Sb 3+ in the V main group, but their corresponding 0D or 2D A 3 B 2 X 9 crystal structure tends to strongly bound excitons, leading to low charge mobility and inferior photovoltaic performance …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Nevertheless, the easy oxidization of Sn 2þ to Sn 4þ and Ge 2þ to Ge 4þ leads to the instability of PSC devices in ambient condition, which remains the biggest challenge in Sn-or Ge-based PSCs. [16][17][18][19][20] In addition to Sn or Ge, another candidate for the substitution of Pb 2þ is non-toxic Bi 3þ and Sb 3þ in the V main group, but their corresponding 0D or 2D A 3 B 2 X 9 crystal structure tends to strongly bound excitons, leading to low charge mobility and inferior photovoltaic performance. [21] Recently, researchers have shown great interest in lead-free double perovskite materials, which possess a crystal structure of elpasolite with a formula of A 2 BB'X 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the heterovalent B-site co-alloying strategy for Pb and Sn, several reports have proposed to mix Sn with Ge for a new candidate of mixture lead-free perovskite. [21][22][23][24][25][26] By first-principles computations, Ju et al predicted several potentially promising mixed Sn-Ge halide perovskites as light absorbers for solar cells. [27] Ma et al presented a comprehensive theoretical study on the mixed vacancy-ordered inorganic double perovskite Cs 2 Sn (1Àx) Ge x I 6 , indicating that the concentration of Ge doping severely influences the thermodynamic, electronic, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Ma et al presented a comprehensive theoretical study on the mixed vacancy-ordered inorganic double perovskite Cs 2 Sn (1Àx) Ge x I 6 , indicating that the concentration of Ge doping severely influences the thermodynamic, electronic, and mechanical properties. [25] Ito et al experimentally showed an improved power conversion efficiency (PCE) of 4.48 % for FA 0.75 MA 0.25 Sn 1Àx Ge x I 3 -based solar cells with a 5 % Ge doping into the perovskite, compared with that (3.31 %) of pure Sn-based ones. [28] Later on, Chen et al reported the first synthesis of CsSn 0.5 Ge 0.5 I 3 bulk crystals via a vapor method, showing a relatively high PCE of 7.11 % but employing a complex, non-scalable, and expensive synthetic route.…”
Section: Introductionmentioning
confidence: 99%